Anti-acetylcholinesterase activity and antioxidant properties of extracts and fractions of Carpolobia lutea - Nwidu, Lucky Legbosi; Elmorsy, Ekramy; Thornton, Jack; Wijamunige, Buddhika; Wijesekara, Anusha; Tarbox, Rebecca; Warren, Averil; Carter, Wayne (Taylor & Francis, 2017)
Context: There is an unmet need to discover new treatments for Alzheimer’s disease. This study determined the anti-acetylcholinesterase (AChE) activity, DPPH free radical scavenging and antioxidant properties of Carpolobia lutea G. Don (Polygalaceae). Objective: To quantify C. lutea anti-AChE, DPPH free radical scavenging, and antioxidant activities, and cell cytotoxicity. Materials and methods: Plant stem, leaves, and roots were subjected to sequential solvent extractions, and screened for anti-AChE activity across a concentration range of 0.02-200 μg//mL. Plant DPPH radical scavenging activity, reducing power, and total phenolic and flavonoid content were determined, and cytotoxicity evaluated using human hepatocytes. Results: C. lutea exhibited concentration dependent anti-AChE activity. The most potent inhibitory activity for the stem was the crude ethanol extract and hexane stem fraction oil (IC₅₀ = 140 μg/mL); for the leaves the chloroform leaf fraction (IC₅₀ = 60 μg/mL/mL); and for roots, the methanol, ethyl acetate, and aqueous root fractions (IC₅₀ = 0.3-3 μg/mL). Dose-dependent free radical scavenging activity and reducing power were observed with increasing stem, leaf, or root concentration. Total phenolics were highest in the stem: ~632 mg gallic acid equivalents/g for a hexane stem fraction oil. Total flavonoid content was highest in the leaves: ~297 mg quercetin equivalents/g for a chloroform leaf fraction. At 1 μg/mL, only the crude ethanol extract oil was significantly cytotoxic to hepatocytes. Discussion and conclusion: C. lutea possesses anti-AChE activity and beneficial antioxidant capacity indicative of its potential development as a treatment of Alzheimer’s and other diseases characterized by a cholinergic deficit.